The consultative style of the high school leader in Riyadh: A comparative study between 1427 AH and 1442 AH - Al-babtain, Abdul Rahman Abdul Wahhab Saud (Journal of Educational and Psychological Sciences, 2021)
This study aimed to investigate the degree of practicing the consultative style of the high school leader from the point of view of secondary school teachers in Riyadh. The researcher used the descriptive approach, and applied it to members of the study sample from secondary school teachers in Riyadh. Their number reached (551) teachers in the first study, and as for the second study, their number reached (125) teachers. The researcher designed the questionnaire as a tool for the study, and among the most important results of this study were the following: -The consultative method in the humanitarian field is practiced by the high school leader in Riyadh to a high degree, while in the fields of study (administrative and technical) it is practiced by the high school leader in Riyadh with a medium degree from the point of view of the teachers of the study sample in the first study. -That the consultative method in the three fields of study (human, technical, and administrative) is practiced by the leader of the secondary school in Riyadh to a high degree, from the point of view of the teachers of the study sample in the second study. - The arithmetic mean in the first study was the degree of the high school leader’s practicing the consultative style in the humanitarian field with teachers (3.41), in the administrative field (3.21), and in the technical field (2.71). -The arithmetic average in the second study reached the degree of the high school leader’s practicing the consultative style in the humanitarian field with teachers (3.47), in the technical field (3.45), and in the administrative field (3.44). -There are no statistically significant differences at the level of (0.05) between the opinions of secondary school teachers about the degree of the high school leader’s practice of the consultative method in the three fields of study (human, administrative, and technical) according to the different study variables (scientific specialization, academic qualification, training programs) , In the first study. -There are no statistically significant differences at the level of (0.05) between the opinions of secondary school teachers about the degree of the high school leader’s practice of the consultative method in the three fields of study (human, administrative, and technical) according to the different study variables: (scientific specialization, academic qualification, experience in the field of Teaching), in the second study. In light of the results of the study, the researcher put forward a number of recommendations.